Pengukuran Kinerja Reksa Dana Syariah Berbasis pada Risiko dan Tingkat Pengembalian - Khoiriyah Trianti; Yulis Nurul Aini; Arif Luqman Hakim; Afifah Nur Millatina; Ludfi Djajanto (Universitas Muhammadiyah Malang, 2022)
This study aims to determine the performance of Sharia Mutual Funds which is very useful for investors in making investment decisions in Sharia Mutual Funds. This research focuses on Fixed Income Sharia Mutual Funds. The research data were obtained from secondary published by the Indonesia Stock Exchange and Bareksa in the form of a report on Net Asset Value and the Rate of Return for the period 2018-2020. The data is analyzed using a risk and rate of return approach which aims to determine the performance of Fixed Income Sharia Mutual Funds. The results reveal that the performance of Fixed Income Sharia Mutual Funds with a risk approach, namely the least risky Fixed Income Sharia Mutual Funds in 2020. By using the rate of return approach, the findings shed a light on the highest Fixed Income Sharia Mutual Funds performance in 2019. Thus, it can be concluded that the performance of Fixed Income Sharia Mutual Funds based on a risk and return approach has a low risk and positive performance.